Traditional law in times of the nation state: Why is it so prevalent? - Jerg Gutmann; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2019)
In many modern nation states, both rich and poor, traditional law to this day plays an important role. Given the almost universal prevalence of traditional law, it is surprising how little we know about it. This is the first study that tries to take stock of traditional law from a cross-country perspective. We are also interested in the compatibility of traditional law with state-enforced law and, in particular, with the basic traits of the rule of law. Based on a sample of up to 134 countries, we find that no "typical" traditional law exists, but that traditional law varies in many dimensions such as its timely enforcement, its impartiality, and its protection of basic human rights. Societies that rely extensively on traditional law score low regarding both the rule of law and per capita income. Historical and geographical factors are important predictors of the contemporaneous reliance on traditional law. State antiquity, for example, reduces the prevalence of traditional law, as does a high share of descendants from European populations.
Keywords: H11; K10; K36; O17; O57; 330; Traditional law; Customary Law; Informal Law; Personal Law; Indigenous Law; Religious Law; Legal Pluralism; Rule of Law; Hybrid Law; Internal Institutions